Masquerading politics : kinship, gender, and ethnicity in a Yoruba town - Willis, John Thabiti, 1976- (African expressive cultures., 2018)
In West Africa, especially among Yoruba people, masquerades have the power to kill enemies, appoint kings, and grant fertility. John Thabiti Willis takes a close look at masquerade traditions in the Yoruba town of Otta, exploring transformations in performers, performances, and the institutional structures in which masquerade was used to reveal ongoing changes in notions of gender, kinship, and ethnic identity. As Willis focuses on performers and spectators, he reveals a history of masquerade that is rich and complex. His research offers a more nuanced understanding of performance practices in Africa and their role in forging alliances, consolidating state power, incorporating immigrants, executing criminals, and projecting individual and group power on both sides of the Afro-Atlantic world.--Publisher's summary.